A Case of Cervical Dystonia - Non Responsive to Usual Noninvasive Treatment (Bangladesh Journal of Anatomy, 2014)
Cervical dystonia is a focal dystonia characterized by neck muscles contracting involuntarily-causing abnormal movement & awkward posture of the head & neck.It is a rare disorder that can occur at any age even infancy.Symptoms generally begin gradually& then reach a point where they dont get substantially worse.Asymmetry of the Sternocleidomastoid is often present in untreated patient.There is no cure for cervical dystonia. Injecting botulinum toxin into the affected muscles often reduce the signs & symptoms of cervical dystonia.Here, it has been described a rare case of a forty seven year old male patient with a history of cervical dystonia presented with struggle with head position, resisting but never overcoming the tendency of his head to assume an unnatural position.The management including drugs like oral analgesic,muscle relaxant,anti-parkinson drug & even antipsychotic drug were used. Phychiatric approach like different modalities of heat such as Short Wave Diathermy, Microwave diathermy & Ultra sound therapy were used. Brace like cervical collar and different types of exercise was also prescribed,even botulinum toxin was injected into suspected muscles but all treatments discussed above failed in this case. DOI: http://dx.doi.org/10.3329/bja.v11i2.20679 Bangladesh Journal of Anatomy, July 2013, Vol. 11 No. 2 pp 92-94